Концептуальна модель життєвого циклу програми - Сухонос, Марія Костянтинівна; Старостіна, Альона Юріївна; Богославець, Аліна Олександрівна (НТУ "ХПІ", 2016)
Запропоновано концептуальну модель життєвого циклу програми. Яка у якості результуючого показника оперує категорією структурної комплексної цінності, причому верхній рівень цінності декомпозується на основі методології Р2М і включає цінності чотирьох груп, а саме: унікальна цінність активу, цінність інновацій, цінність для власників і цінність інтелектуального активу Головною задачею запропонованої моделі є формалізація життєвого циклу програми у розрізі час/результат, що дає змогу підвищити ефективність управління програмою. Також розроблено механізм формування комплексної цінності програми, на основі бальної оцінки, як такої, яка здатна оцінити цінності різної якості за допомогою експертного методу.

A conceptual model of the life cycle of the program is proposed. This model is based on the value approach. As a resulting index it uses a category of complex structural value. This model renders the process of the life cycle of the program in the context of time/result. It assumes the presence of four basic phases of the life cycle, namely, initiation, planning, executing and closing. Also, this model formalizes interconnection of management processes of integration of program and management of its community and subprocesses. Selection of a value approach for the forming of a resulting index of a program determines by a variety of results of program. This is a result of its variety and complexity in the process of finding a criterion for evaluation. Worked out a mechanism for assessing the value of the program. It consists of four steps and involves using of conventional methods (decomposition and expert estimates). As a unit of measurement assumes to use points and rating scale with the maximum score a hundred points. A complex value, which is evaluated at one hundred points, is a result of program. It is critically important in the process of current and final evaluation of the program.
A conceptual model of the life cycle of the program
Keywords: спільнота; цінність; алгоритм; community; value; algorithm